Assessing the effectiveness of China's net-metering subsidies for household distributed photovoltaic systems. (20th July 2020) - Jia, Xinyu; Du, Huibin; Zou, Hongyang; He, Gang
Abstract: Consumer incentives play a vital role in promoting the adoption of renewable energy technology. In China, the government implemented a single, nation-wide net-metering subsidy to cultivate the distributed photovoltaic electricity generation market in 2013 and then had to reduce it twice due to the falling cost of photovoltaic modules and the large resultant financial gap. The aim of this study was to evaluate whether these subsidy adjustments were accurate, and also to identify the factors affecting the subsidy design. We applied a techno-economic evaluation to examine the actual market performance of China's household distributed photovoltaic system in five typical cities with different levels of solar radiation and electricity consumption patterns, and then investigated the subsidy policy's effectiveness through a cost-benefit analysis. The results show that a 3–7 kW photovoltaic capacity in different regions of solar radiation can meet the residential electricity demand. We found that the examination of net-metering effectiveness should consider both regional difference in solar radiation and the different levels of electricity demand. Additionally, the cost-benefit analysis also indicated that a reasonable, regionally differentiated metering subsidy should be in the range of 0.05–0.27 yuan/kWh. Highlights: The market application of China's distributed PV systems is investigated by techno-economic evaluation. The effectiveness of China's net-metering policy for distributed PV systems is examined using cost-benefit analysis. The design of net-metering policy should take regional solar radiation and electric demand into consideration. China's future net-metering subsidy should be designed ranging from 0.05 to 0.27 yuan/kWh. Policy implications are given to promote sustainable development of China's PV industry.